Analisis Efisiensi Penyaluran Kredit pada Lembaga Perkreditan Desa (LPD) di Kecamatan Denpasar Selatan - A. A. Gede Agung Parameswara; I Ketut Darma; Athina Wulandari; Ni Kadek Laksmi Dewi (Warmadewa Economic Development Journal (WEDJ), 2018)
Village Credit Institutions are financial institutions operating in villages that have a role in the development of trade in Pakraman village in Bali Province. This study aims to determine the factors that influence the efficiency of lending carried out by LPDs in South Denpasar District. Determination of samples in this study using saturated sample techniques or census Data collection using questionnaires and research respondents as many as 33 respondents. Data analysis used is validity and reliability test, classic assumption test, and multiple linear regression method. Based on data analysis, it was concluded that the control environment, risk assessment, information and communication, control and monitoring activities had a positive and significant effect on the efficiency of lending to LPDs in South Denpasar District.